2018
DOI: 10.3389/fphys.2018.00847
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Modulates the Sensitivity of Lung Vagal C Fibers in Female Rats Exposed to Intermittent Hypoxia

Abstract: Obstructive sleep apnea is mainly characterized by intermittent hypoxia (IH), which is associated with hyperreactive airway diseases and lung inflammation. Sensitization of lung vagal C fibers (LVCFs) induced by inflammatory mediators may play a central role in the pathogenesis of airway hypersensitivity. In females, estrogen interferes with inflammatory signaling pathways that may modulate airway hyperreactivity. In this study, we investigated the effects of IH on the reflex and afferent responses of LVCFs to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…9 Control of breathing is regulated by central and peripheral chemoreceptors, hormones, autonomic nervous system activation, and other factors that may vary by sex. [10][11][12][13][14] From a pharmacotherapeutic perspective, limited evidence indicates that caffeine efficacy or metabolism may differ in males and females. 15,16 Sex differences in occurrence of the apnea of prematurity or response to caffeine could have broad prognostic and therapeutic implications.…”
mentioning
confidence: 99%
“…9 Control of breathing is regulated by central and peripheral chemoreceptors, hormones, autonomic nervous system activation, and other factors that may vary by sex. [10][11][12][13][14] From a pharmacotherapeutic perspective, limited evidence indicates that caffeine efficacy or metabolism may differ in males and females. 15,16 Sex differences in occurrence of the apnea of prematurity or response to caffeine could have broad prognostic and therapeutic implications.…”
mentioning
confidence: 99%
“…Preclinical experiments support this notion, whereby the hypertensive effects of intermittent hypoxia were more pronounced in ovariectomized rodents relative to females that retained their ovaries [81]. A similar study illustrated that intermittent hypoxia sensitizes lung vagal C fibers to a greater extent in ovariectomized rats relative to those with intact ovaries and that this effect was offset with supplemental 17β-estradiol [82]. While the clinical implications of these findings are not immediately apparent, these data clearly indicate that intermittent hypoxia alters sympathetic discharge patterns differently between sexes and that female sex hormones appear to offset the neurophysiological effects of intermittent hypoxia.…”
Section: Intermittent Hypoxia Studiesmentioning
confidence: 76%
“…The fraction of exhaled nitric oxide (FeNO) measures pulmonary endothelial NO levels and regulates the homeostasis in endothelium showed no increase in Group 2 post hypoxia similar to HAPE-S [ 16 ]. On the contrary, studies showed females having less hypoxia susceptibility related to relatively more NO production due to a direct action of estrogen on vascular endothelium [ 29 , 30 ]. We found evidence of reduced oxidative phosphorylation in Group 2 as GLUT1 level was high during hypoxia, moreover, elevated baseline lactate and no significant fall in PO 2 on acute hypoxia is in contrast to Group 1.…”
Section: Discussionmentioning
confidence: 99%